2019
DOI: 10.3989/mc.2019.12618
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different sources of coal gangue used as aluminosilicate powder on the mechanical properties and microstructure of alkali-activated cement

Abstract: Coal mining wastes are associated with serious environmental problems; they have potential as building materials, including alkali-activated cement. In this study, the effect of different coal mining wastes on the mechanical properties and microstructural development of alkali-activated materials (AAMs) was evaluated through XRD, SEM and FTIR spectroscopy. Different alkali-activated compounds were produced; the alkaline solution was composed of NaOH+Na2SiO3. The results obtained using the calcined coal sludge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 45 publications
(70 reference statements)
0
8
0
Order By: Relevance
“…Sharp diffraction peaks representing quartz (SiO 2 , PDF 00‐046‐1045) and hematite (Fe 2 O 3 , PDF 00‐033‐0664), accompanied by a weak peak of muscovite (KAl 3 Si 3 O 10 (OH) 2 , PDF 01‐075‐0948) and cristobalite (SiO 2 , PDF 01‐082‐0512), were observed in HCG, with a particularly sharp quartz peak at a 2 θ value of ∼26.6°. The broad halo between 20° and 35° in the X‐ray pattern of the AAM indicates the formation of an amorphous sodium aluminosilicate gel (N–A–S–H) during the synthesis of the material 71,72 . As shown in Figure 2A, the main crystalline phases of the HCG and pure AAM powders are essentially identical, with quartz and hematite being the most abundant phases.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Sharp diffraction peaks representing quartz (SiO 2 , PDF 00‐046‐1045) and hematite (Fe 2 O 3 , PDF 00‐033‐0664), accompanied by a weak peak of muscovite (KAl 3 Si 3 O 10 (OH) 2 , PDF 01‐075‐0948) and cristobalite (SiO 2 , PDF 01‐082‐0512), were observed in HCG, with a particularly sharp quartz peak at a 2 θ value of ∼26.6°. The broad halo between 20° and 35° in the X‐ray pattern of the AAM indicates the formation of an amorphous sodium aluminosilicate gel (N–A–S–H) during the synthesis of the material 71,72 . As shown in Figure 2A, the main crystalline phases of the HCG and pure AAM powders are essentially identical, with quartz and hematite being the most abundant phases.…”
Section: Resultsmentioning
confidence: 96%
“…The characteristic absorption bands at 1091, 797, 778, and 695 cm −1 are ascribed to quartz 79–81 . The broad peak at 3441 cm −1 is the characteristic of O–H asymmetric stretching (3000–3700 cm −1 ), which is associated with the formation of hydrated compounds 72,82,83 . The bending vibration of O–H is observed at ∼1626 cm −1 , indicating the presence of water molecules 84–86 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, an increased demand for the appropriate and efficient use of coal gangue has been observed in different sectors. Thus, several studies can be found in the literature aimed at the use of this waste in geotechnical applications [116], alkaline-activated materials [117,118], as zinc and manganese ion adsorbent [119,120] or in agricultural applications [121]. Commonly, coal gangue is composed of a mixture of sandstone, shale and carbonaceous slate, with SiO 2 and Al 2 O 3 as its main chemical constituents.…”
Section: Coal Ganguementioning
confidence: 99%
“…Moreover, the production of cement is a process involving high pollution and energy consumption, which is contrary to the theme of green building materials. The identification of inorganic industrial by-products that can replace Portland cement, and the use of industrial by-products [18][19][20][21] to reduce pollution and the environmental burden, have become research hotspots in environmental protection. The alkali-activated gel material is a mixture of aluminosilicate and alkali metal hydroxide or alkali metal silicate solution [22,23], which is an inorganic polymer.…”
Section: Introductionmentioning
confidence: 99%